Realidade e representação: possibilidade e desafio em pintura - Bellagamba, Mauro Folhadella (1998)
This paper summarizes theoretical considerations engendered by my artistic production in painting. It intends to join practice and reflection, fulfilling the requirements for attaining a Master Degree in Visual Languages. Cutting out brief slices of Art’s History, I try to situate and analyse contexts and moments when the questioning of values (as occurs today) evoked in artists and their work answers in an attempt to overcome feelings of doom and end - comprising movements I call ideological acts. In favor of a starting hypothesis which defends the maintenance of painting and its procedures as a legitimate way of working out poetic creation in our time, I present four of my own paintings which, besides depicting concepts such as Reality and Representation, Part and Whole, Intention and Gesture, hold the directions of my wonderings in today’s artistic context.